2-Year field operation monitoring of electrostatic precipitators for residential wood heating systems. (April 2018) - Brunner, Thomas; Wuercher, Gerald; Obernberger, Ingwald
Abstract: To assess the applicability of electrostatic precipitators (ESP) for particulate matter (PM) emission reduction in old residential wood heating appliances comprehensive field tests with accompanying ESP operation monitoring and dedicated emission measurement campaigns have been performed in the region of Graz (AT). Three OekoTube ESPs were thereby tested during the heating seasons 2014/2015 and 2015/2016 at different sites with rather old respectively high-PM-emission wood burning devices. Before installing the ESPs at the field testing sites they were checked in the lab regarding functionality and precipitation efficiency. The evaluation of the plant monitoring data collected during the field tests revealed high seasonal ESP availabilities between 80.2% and 97.7%. Dedicated test runs with emission measurements at the different testing sites showed high precipitation efficiencies which were well comparable with those gained during preceding lab-tests. Based on these results it can be concluded, that ESP models like the OekoTube are suitable as retrofit units in old appliances and have due to their high availability and particle precipitation efficiency the potential to contribute to a significant reduction of particulate matter emissions from old residential wood burning systems. Highlights: Test of three ESPs at old residential wood combustion systems over two heating seasons. Collection of a huge set of plant operation data during a continuous 2 year monitoring. Comprehensive evaluation of the plant monitoring data to analyse the ESP operation. Data from two dedicated emission measurement campaigns per heating season and ESP. Comprehensive data on ESP operation, availability and emission reduction efficiency.